Accountability - Nkoana, Katlego (WritingThreeSixty, 2025)
Everyone wants to be bejewelled With the shine stones of victimhood The glimmer so blinding absolving anyone to see the dim of the truth Leaning into the luminous sun Forgetting it’s simmer Till tipping point